CRYOTOLERANCE OF SPERMATOZOA VARIES ACCORDING TO THE BREED OF GOAT - Bogdaniuk, A.; Petrushko, M; Garkavii, V (My University, 2023)
Cryotolerance of spermatozoa depends on the breed of goats. Although motility, viability and morphological characteristics of fresh spermatozoa are better in Alpine breed, after cryopreservation the decrease of these parameters is lower in Saanen breed
Bogdaniuk AO, Petrushko MP, Garkavii VV Cryotolerance of spermatozoa varies according to the breed of goat. Актуальні питання ветеринарної медицини: реалії та перспективи: збірник тез доповідей всеукр. наук.-практ. конф. науковців, викладачів та аспірантів, 23 травня 2023 р. Харків: ДБТУ, 2023. С. 26-27
Keywords: sperm; cryopreservation; goat